(untitled) (Advances in Knowledge Representation, 2021)
Ontologies are artifacts used by Information Science professionals, to represent knowledge in digital platforms. Those artifacts are shining due to its representation features like entity relationships and using descriptive logic to be machine-readable. However, there are few ontologies made by Information Science professionals that use descriptive logic. To address this context, the present paper has as objective, familiarize the Information Science professionals with logic. To achieve this, the concepts of descriptive logic is presented to the reader and how it is linked with knowledge representation models to validate models and to reason new knowledge. The contributions of this paper is to provide a model to formalize natural language in logic and provide ten guidelines of how to incorporate logic in ontologies. Lastly, this paper suggests as future work to embody those guidelines into an ontology methodology as the best way to consolidate the use of logic within the applied ontology context.